Effect of balanced use of nutrients on yield attributes, yield and protein content of wheat (Triticum aestivum) - TRIVEDI, VIVEK KUMAR; RAZA, MD BASIT; DIMREE, SUSHIL; VERMA, ANIL KUMAR; PAWAR, ATUL BHAGAWAN; UPADHYAY, DEVI PRASAD (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was carried out with wheat in rabi season of 2015-16 at Nawabganj Research Farm, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh, India to study the effect of balanced use of nutrients on yield, yield attributing characters, uptake of nutrients and quality of wheat grain. A field experiment was conducted with 10 different treatment combinations comprising of different levels of N, P, K, S and Zn. Results revealed that the combined application of S@40 kg/ ha and Zn@5kg/ ha along with 125% NPK (T9) proved to be the best nutrient management option for getting higher yield with better grain protein content and quality. Combined use of S and Zn along with 125% NPK produced highest biological yield (130.63 q/ha) which was 66% higher than 100% NPK treatment. Significant increase in yield attributing characters and nutrient uptake (N, P, K, S and Zn) was also observed under T9 treatment. As far as nutritional quality of wheat grain is concerned, about 22% higher protein content was found in wheat grain with T9 treatment over control.